Fabricación de piezas de alúmina mediante fotocurado UV : diseño y evaluación suspensión cerámica (2017)
It is possible to create ceramic parts through stereolithograpy methods with accuracy and good mechanical properties (density, hardness, among some), using a curable suspension and making a layer by layer construction of the green body. In this study alumina parts of simple geometry were fabricated through photopolymerization of an aqueous suspension. Two suspensions with different powder size (300 nm y 700 nm) were created and their stability was evaluated. Similarly different drying processes of the green bodies were compared. The experimental results show that it is possible to obtain a stable suspension over the course of time with the bigger ceramic particles unlike the suspension with the other particles. Equally it can be noticed that when a liquid desiccant is used it is possible to keep the bodies geometries and there's no distortions in the bodies in comparison with an air drying. The sintered bodies show good mechanical properties...